Comparison of the Effectiveness of Artificial Intelligence-Based Plant Recognition Applications - Kozma-Bognár, Kristóf; Berke, József; Anda, Angéla; Kozma-Bognár, Veronika (GEORGIKON FOR AGRICULTURE, 2024)
With the development of technology, more and more artificial intelligence-based plant recognition software is being developed, which can make it easier to determine the plants living in our environment. The aim of our work was to compare the effectiveness of different plant recognition software. We chose Kísérleti lake and its immediate surroundings in the area of Stage I (Hídvégi lake) in Kis-Balaton in the year 2024. In connection with machine vision, the task of the device was to detect the plant, separate it from the plants representing the background, and based on its individual characteristics, make a decision about exactly what kind of plant it is. During the research, we compared six different plant recognition applications by analyzing 15 images of plant species typical of the area. The plants appeared as a simple tool in the experiment, with which the comparison of applications could be realized. The main aspect of their selection was that the input data set should contain simple plants with almost the same color as the background, as well as plants with unique, colorful inflorescences. We checked the accuracy and compared the results with the values indicated by the developers of the software. Based on the results, we determined which application is recommended for the accurate recognition of plants in this region.